A framework to expand public health services to HIV exposed and HIV positive children - Reid, Marianne (University of the Free State, 2009)
The aim of this study was to develop a framework to expand public health care services to HIV exposed and HIV positive children in the Free State. The objectives set in order to meet the aim were to identify strategies to expand health care services to these children and to then develop a framework to expand health care services to them within the Free State public health sector. The study consisted of various component projects, depicted as phases. The researcher conducted two components, Phase 1b and Phase 2 which links to the fore mentioned objectives of the study. A colleague, conducting research as Master student, conducted Phase 1a of the study, describing health care services rendered to HIV exposed and HIV positive children in the Free State public health sector. The researcher was intimately involved in Phase 1a, as she was acting as co-study leader. Health policy research was used, which is a type of health systems research, in an effort to inform higher levels of health on policy choices. Health managers were therefore active stakeholders in the development of the framework. The identification of strategies to expand health care services to HIV exposed and HIV positive children were one such activity where stakeholders assisted in the development of the framework. The Nominal Group Technique was used to identify mentioned strategies. A draft framework was developed using the Theory-of-Change Logic model as theoretical underpinning of the framework, with the empirical foundation being based on triangulated data obtained from literature findings, Phase1a and Phase 1b of the study. During a workshop with stakeholders, the framework was finalized, providing stakeholders the opportunity to validate the identified problem, namely that of fragmented care being delivered to HIV exposed and HIV positive children, due to over-verticalisation of programs. The validation of the framework was completed by confirming the desired results, possible influential factors that could impact on the results, as well as strategies that could be followed to expand health care services to fore mentioned children. Since health policy research only informs policy choices, the extent to which the framework will actually inform policy is in the hands of the Free State Department of Health.
Thesis (D.Soc. (Nursing))--University of the Free State, 2009
Keywords: Public health -- South Africa -- Free State; HIV infections -- South Africa -- Free State; Medical policy -- South Africa -- Free State